Biopterin in Parkinson's disease. Issue 1 (January 1987) - Moore, A P; Behan, P O; Jacobson, W; Armarego, W L
Abstract : Tetrahydrobiopterin is an essential co-factor in the natural synthesis of dopamine. Oral tetrahydrobiopterin was given in small doses to four patients with early Parkinson's disease but had no discernible effect.